Advances and Perspectives of Transgenic Technology and Biotechnological Application in Forest Trees - Yin, Yiyi; Wang, Chun; Xiao, Dandan; Liang, Yanting; Wang, Yanwei (Frontiers in Plant Science, 2021)
Transgenic technology is increasingly used in forest-tree breeding to overcome the disadvantages of traditional breeding methods, such as a long breeding cycle, complex cultivation environment, and complicated procedures. By introducing exogenous DNA, genes tightly related or contributing to ideal traits—including insect, disease, and herbicide resistance—were transferred into diverse forest trees, and genetically modified (GM) trees including poplars were cultivated . It is beneficial to develop new varieties of GM trees of high quality and promote genetic improvement of forests. However, the low transformation efficiency has hampered cultivation of GM trees and identification of the molecular genetic mechanism in forest trees compared to annual herbaceous plants such as Oryza sativa. Here we review advances in transgenic technology of forest trees, including the principles, advantages and disadvantages of diverse genetic transformation methods, and their application for trait improvement. The review provides insight into the establishment and improvement of genetic transformation systems for forest tree species. Challenges and perspectives pertaining to the genetic transformation of forest trees are also discussed.